Carbon dioxide conversion technologies to formic acid and methanol promoted by ionic liquid. - Bello, Taofeeq Oladayo (2022)
Carbon dioxide (CO2) can be recycled as a carbon building block to produce organic chemicals as a waste product. However, CO2 is thermodynamically and kinetically difficult to transform because of its stability. The conditions and parameters must be viable to circumvent the bottleneck of the process conditions and performance parameters. Hence, the proposed study aims to find innovative methods in terms of improving the yield and reducing the energy requirement for the favourable production of formic acid and methanol simultaneously from CO2, subsequently improving its economic value and finally reducing its impact on the environment. Ionic liquids have been used as a suitable solvent for the conversion of CO2 to various organic products. Their excellent characteristics, such as low pressure, high turnability, and stability, have allowed them to be used in many fields. A series of cations and anions were randomly paired through a theoretical approach. The conductor-like screening model for real solvent (COSMO-RS) was employed to predict thermodynamic, physical, and toxicity properties. From 240 ionic liquids (ILs), four ILs were finally selected for a continuous process evaluation by Aspen Plus. The result showed a high tendency for CO2 absorption capacity and lower energy consumption. The process simulation through Aspen simulator shows the reaction\'s feasibility with the selected ionic liquid. The results revealed a high CO2 conversion of up to 80% conversion of CO2 per pass and improved yield of formic acid at low temperature and moderate pressure. Economic metrics of the plant showed that the process profitability largely depends on the source (cost) of H2 and the selling price of formic acid. A profitable process plant is achievable at a hydrogen price of 1.5USD/Kg and a minimum selling price of 0.935USD/Kg of formic acid. A mechanistic approach through quantum chemical calculation (DFT) was conducted to further understand the reaction\'s insight. Thermochemical and kinetic data were also evaluated. The results showed that a negative Gibbs energy was achieved when the reaction is promoted by an IL, which affirmed the process simulation results. However, since the ionic liquid is not yet available commercially, further experimental work is needed to get insight into the kinetic behaviour of the IL in the reaction in terms of the breakage of H2 bond and formation of intermediates reaction.